2018
DOI: 10.22271/ortho.2018.v4.i1m.128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramedullary nail removal after tibial fracture repair: A prospective study

Abstract: Introduction: Tibial fractures are the most common long bone fracture. The standard of care for the treatment of diaphyseal tibial fractures is an intramedullary nail (IMN). Implant removal is one of the most common procedures in bone and joint surgery, and criteria for implant removal are typically left to the treating surgeon. We conducted a prospective study to investigate effects of intramedullary nail removal after tibial fracture union. Methods: Sixty patients at our hospital were enrolled in a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is one reason why studies focus on the improvement of osseointegration, in contrast to this study [52][53][54]. However, many studies describe complications during intramedullary nail removal or the need for special instruments [55][56][57]. Therefore, in recent decades, some studies have also focused on reducing osseointegration, like Levanus et al, who showed a decreased osteocalcin and collagen 1 expression after cultivation on Ti300 substrates, a titanium surface with 300 nm pores [58].…”
Section: Discussionmentioning
confidence: 86%
“…This is one reason why studies focus on the improvement of osseointegration, in contrast to this study [52][53][54]. However, many studies describe complications during intramedullary nail removal or the need for special instruments [55][56][57]. Therefore, in recent decades, some studies have also focused on reducing osseointegration, like Levanus et al, who showed a decreased osteocalcin and collagen 1 expression after cultivation on Ti300 substrates, a titanium surface with 300 nm pores [58].…”
Section: Discussionmentioning
confidence: 86%
“…Especially for metal implants in load-bearing regions, increased bone formation and accelerated tissue integration seem reasonable. Nevertheless, several studies describe complications during nail removal through nail failure, jamming in the fracture callus during removal, or difficulties and need for special instruments [46][47][48]. Most studies of modified surfaces focused on increased cell adhesion/osseointegration [39,[42][43][44][45] or decreased bacteria adhesion/prevention of biofilm formation [49][50][51].…”
Section: Discussionmentioning
confidence: 99%